2019
DOI: 10.1186/s12885-019-6126-y
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab use in older patients with HER2-positive metastatic breast cancer: outcomes and treatment patterns in a whole-of-population Australian cohort (2003–2015)

Abstract: Background Older patients with HER2-positive metastatic breast (HER2 + MBC) cancer are underrepresented in clinical trials. We aim to describe the treatment patterns and overall survival (OS) for older women receiving trastuzumab for HER2 + MBC. Methods Retrospective, whole-of-population cohort study using demographic, dispensing, and medical services data for Australian women ≥ 65 years initiating trastuzumab for HER2 + MBC between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…The proportions of patients in our cohort 65 years and older (31%) and 75 years and older (11%) were notably larger than that reported from EMILIA. Older patients represent a growing proportion of patients treated with HER2-targeted agents [17] and recent Canadian real-world cohorts (of similar size to ours) from Ontario and Alberta reported median ages closer to our cohort (56 and 58 years, respectively [18,19]).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The proportions of patients in our cohort 65 years and older (31%) and 75 years and older (11%) were notably larger than that reported from EMILIA. Older patients represent a growing proportion of patients treated with HER2-targeted agents [17] and recent Canadian real-world cohorts (of similar size to ours) from Ontario and Alberta reported median ages closer to our cohort (56 and 58 years, respectively [18,19]).…”
Section: Discussionsupporting
confidence: 76%
“…These differences in may be due to the older age of our population and the large proportion of our cohort receiving (neo)adjuvant trastuzumab therapy. Previous research, including our own, has shown shorter OS for patients 65 years and older [ 17 ], as well as worse outcomes in the metastatic setting associated with HER2-targeted therapy in patients previously treated with (neo)adjuvant trastuzumab [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there exists a controversy regarding whether women aged ≥ 80 years benefit from locoregional control as much as younger women, especially in patients that present with distant metastases. Additionally, another explanation might be that potential targeted therapy was associated with improved survival among patients aged < 65 years [28]. In fact, several retrospective studies have shown that the benefits and safety of optimal treatment were maintained in patients aged > 75 years [8].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the ageing population, the number of elderly BC patients is rising. Despite this, elderly patients have been consistently underrepresented in clinical trials [7][8][9]. Only 16% of patients in the pivotal trials of adjuvant trastuzumab therapy were over 60 years old [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Set thresholds of chronological age, which de ne a patient as elderly, also vary from ≥ 65 [13,14], ≥ 70 [15][16][17] to ≥ 75 [5,18] or even ≥ 80 years old [19], which complicates comparisons between studies. Furthermore, older participants in randomised controlled trials (RTCs) may be tter than the wider elderly population [7][8][9]. Thus, the application of current treatment recommendations in elderly patients outside clinical trials can be limited due to the cardiotoxic nature of anthracycline-based chemotherapy and HER2-targeted therapy [8,9,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%